1994
DOI: 10.1213/00000539-199404000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Mechanisms for Clonidine Reversal of Bupivacaine-Induced Impairment of Ventricular Conduction in Pentobarbital-Anesthetized Dogs

Abstract: Possible mechanisms of the ability of clonidine to correct bupivacaine-induced ventricular electrophysiologic impairment were evaluated in an electrophysiologic model on closed-chest dogs. Nine groups (n = 6) of pentobarbital-anesthetized dogs were given atropine, 0.2 mg/kg intravenously (i.v.), and bupivacaine, 4 mg/kg i.v., over a 10-s period. Group 1 was then given only saline solution. Group 2 was given clonidine, 0.01 mg/kg i.v., over a 1-min period. Group 3 was given clonidine followed by i.v. administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In animal studies, De la Coussaye and co‐workers have shown that administration of intravenous clonidine can counteract the myocardial conduction abnormalities caused by local anaesthetics ( 24, 25). If an accidental intravenous injection of local anaesthetic takes place clonidine will in this case be simultaneously injected together with the local anaesthetic, and this could potentially increase the myocardial tolerance to local anaesthetic induced arrhythmia.…”
Section: Discussionmentioning
confidence: 99%
“…In animal studies, De la Coussaye and co‐workers have shown that administration of intravenous clonidine can counteract the myocardial conduction abnormalities caused by local anaesthetics ( 24, 25). If an accidental intravenous injection of local anaesthetic takes place clonidine will in this case be simultaneously injected together with the local anaesthetic, and this could potentially increase the myocardial tolerance to local anaesthetic induced arrhythmia.…”
Section: Discussionmentioning
confidence: 99%
“…Although many drugs, such as magnesium, 12 clonidine, 13 and hexamethonium, 14 have been reported to have a beneficial effect on bupivacaineinduced arrhythmias in experimental studies, their mechanisms have remained speculative. More importantly, these drugs have not been reported to be clinically effective.…”
Section: Discussionmentioning
confidence: 99%
“…An animal study demonstrated partial improvement in bupivacaine-induced intracardiac conduction delays following clonidine administration (0.01 mg/kg IV), but nonperfusing rhythms were not studied (LOE 5). 514 …”
Section: Consensus On Sciencementioning
confidence: 99%